#TITLE_ALTERNATIVE# - Fajar Syaifulloh (NIM 19004105), Aryo
ABSTRACT: Stock is one of the investment facilities that many investors are interested about. The stocks value is dynamically fluctuated, therefore stock can be counted as a high risk investment and expected to gain high profit also. The whole stocks movement/fluctuation is represented by a market index which is called IHSG. Besides IHSG there is a market index, that only consisted by the top 45 of the most liquid stock and which had has a big market share, called LQ 45. In this final project, both IHSG and LQ45 becomes an indicator to determine the expected return of a sectoral stock. It is interesting to know which market index that can be used to determine the expected return of a sectoral stock more precise, IHSG or LQ45. Because by knowing the better option, not only investor could minimize the risk that would be taken but also could maintain the expected return at a high point. To reveal that matter above, in this final project, hypothesis testing are being done by taking the data from time series method with a CAPM approach on the daily closing price of a sectoral stocks of mining, property and real estate, finance and miscellaneous for the January 2002 to December 2006 period. From the calculated results, it is shown that both market index, IHSG and LQ45, can be used to determine the expected return of property and real estate stock. For finance and miscellaneous, LQ45 could determine better than IHSG and on the contrary, IHSG determine better than LQ45 on the mining sector. For the further research, it is recommended to perform a research that concern more about individual stocks that are followed with analysis, including market capitalization and volume, and also to review how far this research method (CAPM) can be used to determine the expected return if there are more data is being added, is there any change or not.